THE INFLUENCE OF UNEMPLOYMENT AND LACK OF LEGAL INCOME ON THE INCREASE IN PROPERTY CRIME - Danang Rahmat Surono; Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the influence of unemployment and lack of legal income on the increase in property crime through a literature review method. Unemployment and lack of legal income are two economic and social factors that contribute significantly to individuals committing property crimes, such as theft, robbery, and embezzlement. The literature review shows that unemployment creates strong economic and social pressures, while the absence of legal income narrows opportunities to earn a legitimate income, thereby encouraging criminal acts as an alternative. This study concludes that reducing unemployment and increasing access to legal income through effective economic and social policies are essential to reducing property crime rates and improving community welfare.